Optimization of Fastness Properties with Gray Relational Analysis Method in Dyeing of Hemp Fabric with Natural and Classic Mordant - ÖZOMAY, MERAL (TAYLOR & FRANCIS INC, 2022)
Although natural fibers used to be colored with natural dyes, today they have been replaced by chemical dyes and our cultural values have been abandoned. Metal salts harm both the nature and the human beings more than synthetic dyes do. This study examines the effects of both natural and chemical mordants on dyeing as well as the use of natural dye obtained from Sambucus Ebulus L. plant for dyeing Hemp fabric. In this study 100% hemp fabric was dyed with 15 different concentrations of 3 different mordant substances one of which was natural. Lightfastness and washing features of dyed hemp samples were done then color differences and color efficiency calculated by CIE L*a*b color space system were compared. For the optimization of dyeing parameters Grey Relational Analysis (GRA) method was used. Being one of the multi-criteria decision-making methods, GRA is the alternative and the most effective approach that can be employed in case of insufficient or discrete information, too much data, and vagueness. Experimental results show that the use of the natural mordant in dyeing the hemp fabric with Sambucus Ebulus L. plant gives better results in terms of color difference and color efficiency.
Keywords: Grey Relational Analysis; sambucus Ebulus L; rize Regional Fabric; natural Dying; natural mordant; hemp; COTTON; SILK; DYES; EXTRACTION